Small-Strain Dynamic Properties of Lean Cemented Sand and Gravel Materials under Different Cementing Agent Contents - Jie Yang; Xin Cai; Yangong Shan; Miaomiao Yang; Xingwen Guo; Jinlei Zhao (Advances in Civil Engineering)
Lean cemented sand and gravel (LCSG) materials are increasingly being used in dams, embankments, and other civil engineering applications. Therefore, their mechanical properties and stress-strain behavior should be systematically understood. In this study, the small-strain dynamic properties of LCSG materials were examined. A series of dynamic triaxial tests were performed to investigate the effects of the confining pressure and cementing agent content of the material on its dynamic shear modulus (Gd) and damping ratio (λ). The results show that Gd increased and λ decreased with increasing confining pressure and cementing agent content; however, under the same confining pressure and cementing agent content, Gd decreased gradually in accordance with shear strain. Furthermore, new expressions were derived for Gd and λ, as well as for their maxima. The results of this study could provide a reference for practical engineering applications, including the construction of dams using LCSG materials.